High diversity of native plants and vegetation types in the Morialta Conservation Park and the threat of invasive species. Issue 2 (2nd July 2020) - Anderson, J.; Keppel, G.; Thomson, S.-M.; Gibbs, J.; Brunetti, G.
ABSTRACT: Morialta Conservation Park is a scenic protected area that contains important vegetation remnants of the Mount Lofty Ranges. Here we investigate the vegetation ecology, soils and plant diversity of the park. Using a stratified, quantitative survey of woody vegetation and topsoils throughout the park within forty-five 10 × 10 m plots, we identified ten distinct vegetation types, nine being native and the other being dominated by the invasive European olive ( Olea europaea ). Soil conductivity and fertility, as well as aspect, were significant predictors of species composition, indicating that high environmental heterogeneity in soils and topography are important in facilitating the high biodiversity in the Morialta Conservation Park. The European olive and Boneseed ( Chrysanthemoides monilifera ssp. monilifera ) are widespread in the park and a threat to native vegetation. Using published plant lists and the Atlas of Living Australia, we report 486 native (and 300 introduced) plant taxa from the park and its immediate surrounds, including species considered endangered at either the state or national level, or the IUCN Red List. Therefore, the park is highly important for conservation and the threat posed by the European olive, Boneseed and other invasive species should be effectively managed.